The Municipal Mouncil in the Ecuadorian Legislation - Arroyo Preciado, Alberto (Revista Universidad de Guayaquil, 2012)
“The Municipal Council in the Ecuadorian Legislation” I am realised doctrinary from the birth of the municipality as well as from the legislation of the Consistorial Organ of the Ecuadorian municipality and other countries of Hispanic speech that in the course of this proposal will talk about it. This work of academic investigation, has as an aim, to express the thematic policeman, like also contributing to the development of the municipal right of Hispano-America, to the enrichment of the general performances, historical and present of the municipality as well as, the most excellent aspects of its legal frame - Constitution of the Republic of Ecuador - Organic Code of Territorial organization, Autonomy and Decentralization COOTAD, aspects that are necessary that they are known by the administered one. The figure of the municipal government, as cell of the local public administration has been evolving of well-known way in the country and in the world, of this form, in the present work I allow myself to express the exercise of the authority and the public powers of the independent governments decentralized policemen the same one who will be in force by the principles of: “Unit; Solidarity; Coordination; Joint responsibility; Subsidiarity; Complementariness; Interterritorial fairness; Citizen Participation and Viability of the Development”